Process of Making Gas Stove Spuyer with TU-2A CNC Machine - Thomas Djunaedi; Anwar Ilmar Ramadhan; Firmansyah Firmansyah; Mohd Amiruddin Fikri (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2022)
The TU-2A CNC machine is a turning machine tool that is controlled by a computer system through data (program input) in the form of letters and numbers. This machine is capable of producing a work piece with a complex shape and high accuracy, as well as the effectiveness of minimum production time. Gas stove nozzle is a form of work piece which in the manufacturing process is required to have a high level of effectiveness with high accuracy. The supporting factors in the manufacturing process are based on the selection of program functions and machining parameters (cutting speed, feeding, feeding speed and proper rotation of the main axis).In the process of making gas stove nozzles using a CNC TU – 2A machine, the parameter values used are cutting speed (Vs) 20 m/min, feeding 0.75 mm/put, feeding speed (s') 281 mm /min and the main axis rotation (n) 375 rpm.So from the parameters used, it is known that the total machining time per component (tm) = 5.4 minutes, the total production cost per component (Cprod) = Rp. 8,572, - and the total production time per component (t prod) = 7.6 minutes. The greater the value of the Dept of cut, feed and feeding speed, the production time and production costs that occur will decrease until they reach t = 2.6% and C = 2.3%.